Ethical issues in monitoring and based tracking systems - Khalifa, Othman Omran; Chebil, Jalel; Hassan Abdalla Hashim, Aisha; Hameed, Shihab A. (IIUM Press, 2011)
Monitoring and based tracking systems use a variety of technologies to record and monitor the activities of humans. This can increase the risks to the privacy and security of individuals. The amount of information gathered about individuals is growing through the proliferation of surveillance cameras, sensors; microchips and Radio Frequency Identification RFID tags embedded in devices and products. Advances in electronic technologies allow companies and government agencies to store and process large amounts of information about individuals. The Internet provides the ultimate copier device, making this information easily available to millions. This paper highlights the ethical issues emerging with the new technologies in the monitoring and base tracking system. New regulations should be proposed to protect the individual privacy.